ANALISIS PEMILIHAN SUPPLIER DAN PENENTUAN JUMLAH PEMBELIAN BAHAN BAKU DENGAN MENGGUNAKAN METODE ANALYTIC NETWORK PROCESS (ANP) - Citra Indah Asmarawati; Sadiq Ardo Wibowo (Universitas Putera Batam, 2021)
PT. Guna Kemas Indah in determining the supplier of raw materials, but the existing criteria are not sufficient to meet the expected criteria. By using Analytical networking process (ANP) and goal programming in determining quality. In addition, it can also be seen how much raw material purchases are based on the selected supplier. Selection of suppliers is based on several criteria using vendor performance indicators, which are arranged based on sub-criteria. Where the existing subcriteria can influence each criterion. Based on the weight calculation for the criteria are success-quality (0.3868), cost (0.3668), delivery (0.1256), flexibility (0.0619), responsiveness (0.0586) so that 3 supplier candidates will be obtained.